MAMARDASHVILI: SPEECH AS AN EVENT OF THOUGHT - Dmitry G. Ryndin (Moscow Polytechnic University, 2016)
The author deals with the philosophy of M.K. Mamardashvili from the perspective of one of its central concepts, namely the concept of «event». The article presents an attempt to review the features of style of Mamardashvili's philosophical speech with regards to the correspondence of the form and content: philosophical speech as a speech about the event should itself be event-al. The following L.S. Vygotsky's phrase acts as a guiding thread: the thought is not expressed in speech, it happens in it. The analysis is largely based on Vygotsky's concept of inner speech and ideas of philosophical text as «inner speech as an open text» by V.S. Bibler. The article briefly describes how Mamardashvili shows the expressed idea through the very form of his speech. Philosophy, therefore, presents itself as an extremely honest thinking, where the form must correspond to content. Mamardashvili not only highlights the problem of event, but it is also an event to us.